2019
DOI: 10.1016/j.ejca.2019.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events associated with encorafenib plus binimetinib in the COLUMBUS study: incidence, course and management

Abstract: Background: Dual inhibition of the mitogen-activated protein kinase pathway with BRAF/MEK inhibitor (BRAFi/MEKi) therapy is a standard treatment for BRAFV600mutant metastatic melanoma and has historically been associated with grade III pyrexia or photosensitivity depending on the combination used. The objective of this study was to fully describe adverse events from the COLUMBUS study evaluating the most recent BRAF/MEK inhibitor combination encorafenibþbinimetinib. Patients and methods: Patients with locally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 24 publications
1
71
0
4
Order By: Relevance
“…Among the AE, the largest difference between these combined therapies was observed for pyrexia. Indeed, the incidence of pyrexia was lower with E + B combined therapy than with D + T combined therapy (18% vs 52%) 1,2 . Notably, except for one patient, a clinical study on E + B combined therapy did not include patients who were pretreated with anti‐PD‐1 antibody, 2 suggesting the different immunological background in advanced melanoma patients between a clinical study and the actual clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the AE, the largest difference between these combined therapies was observed for pyrexia. Indeed, the incidence of pyrexia was lower with E + B combined therapy than with D + T combined therapy (18% vs 52%) 1,2 . Notably, except for one patient, a clinical study on E + B combined therapy did not include patients who were pretreated with anti‐PD‐1 antibody, 2 suggesting the different immunological background in advanced melanoma patients between a clinical study and the actual clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…As several clinical studies have suggested, the subtypes of serious AE differed between BRAF inhibitor monotherapy and BRAF plus MEK inhibitor combined therapy 1,2,4,11 . The incidence of severe pyrexia, chills, diarrhea and vomiting that may be caused by MEK inhibitors was higher with combined therapy than with BRAF inhibitor monotherapy 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although arthralgia is a common adverse event associated with encorafenib and binimetinib, arthritis has yet to be reported. 1 I describe a case of inflammatory arthritis induced by encorafenib and binimetinib, which has not been observed with other BRAF/MEK inhibitors (dabrafenib and trametinib).…”
mentioning
confidence: 91%